Infrequent Large Nominal Devaluations and their Impacton the Futures Prices for Foreign Exchange in Brazil. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper discusses the behavior of futures prices for foreign exchange in Brazil during a period of high inflation and successive stabilization attempts (1989-92). After testing for futures prices unbiasedness and predicability by applying the Generalized Method of Moments, the paper argues that the finding of excess returns may be viewed as a rational response to the frequent and unpredictable changes in the exchange rate policy during that period. This response could reflect (i) an informational problem where the exchange rate policy is assumed to be unknown; or, (ii) a 'peso' problem of rational (under) overprediction where the futures bias is the market response to the known policy of infrequent large nominal devaluations. The second line of explanation is suggested by conditioning the probability distribution of the excess return of futures contracts on the event of a major devaluation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet